Re-conceptualising VET : responses to covid-19 - Avis, James [Verfasser]; Atkins, Liz [Verfasser]; Esmond, Bill [Verfasser]; McGrath, Simon [Verfasser] (My University, 2021)
"The paper addresses the impact of Covid-19 on vocational education and training, seeking to discern the outline of possible directions for its future development within the debates about VET responses to the pandemic. The discussion is set in its socio-economic context, considering debates that engage with the social relations of care and neo-liberalism. The paper analyses discourses that have developed around VET across the world during the pandemic, illustrating both possible continuities and ruptures that may emerge in this field, as the health crisis becomes overshadowed in public policy by the prioritisation of economic recovery and social restoration. The paper concludes that, alongside the possibility of a narrowing of VET to its most prosaic aims and practices, the health crisis could also lead to a re-conceptualisation that develops its radical and emancipatory possibilities in both the global south and north." (Author's abstract ; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; 370; Pandemie; Berufsausbildung; Konzeption; Zukunftsperspektive; Wirtschaftsförderung